2023
DOI: 10.1021/acs.macromol.2c02291
|View full text |Cite
|
Sign up to set email alerts
|

Polyfluorenes Bearing N,N-Dimethylpiperidinium Cations on Short Spacers for Durable Anion Exchange Membranes

Abstract: Alicyclic quaternary ammonium cations having all the β-protons in a strain-free ring structure are in general highly base-resistant and are thus very attractive to employ for anion exchange membrane (AEM) applications. However, tethering cations such as N,N-dimethylpiperidinium (DMP) to polymer backbones without introducing any weak links is quite challenging. In the present study, we have attached pairs of piperidine rings in their 4-position to fluorene and 2,7-diphenylfluorene via methylene bridges using st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The chemical stability of the AEMs and ionomers under harsh alkaline conditions is an important topic of current research. Their stability is mainly determined by the structure of the polymer backbone, side chain, and cationic head groups. , The alkaline stability of the prepared ionomers was first evaluated by monitoring the changes of OH – conductivity during the treatment in a 1 M NaOH solution at 80 °C. For the CF 3 -substituted series, the OH – conductivity remained stable throughout the alkaline stability test (Figure a), indicative of excellent chemical stability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The chemical stability of the AEMs and ionomers under harsh alkaline conditions is an important topic of current research. Their stability is mainly determined by the structure of the polymer backbone, side chain, and cationic head groups. , The alkaline stability of the prepared ionomers was first evaluated by monitoring the changes of OH – conductivity during the treatment in a 1 M NaOH solution at 80 °C. For the CF 3 -substituted series, the OH – conductivity remained stable throughout the alkaline stability test (Figure a), indicative of excellent chemical stability.…”
Section: Resultsmentioning
confidence: 99%
“…The existence of enough water molecules in the ionomer not only is conducive to ion dissociation but also facilitates the rapid migration of ions in the percolating water-rich phase domain . Generally, the WU and SR are directly related to the IEC values, but there are outliers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclic ammoniums, especially piperidinium and spirocyclic ammoniums, have recently become an increasingly frequent choice of cation for implementation in AEMs. ,, In this study, the effect of ring size on conductivity and stability was determined by comparing ammoniums containing a 5-, 6-, or 7-membered ring ( PE14 , PE15 , PE16 ) (Scheme ). It was observed that the 6-membered piperidinium ring exhibited the highest conductivity stability followed by the 5-membered and then the 7-membered ring ( PE15 > PE14 > PE16 ) with 95, 44, and 15% conductivity retention, respectively (Figure d, Table ).…”
mentioning
confidence: 99%